Qiangji Decoction Alleviates Neurodegenerative Changes and Hippocampal Neuron Apoptosis Induced by D-Galactose via Regulating AMPK/SIRT1/NF-κB Signaling Pathway - He, Li-Ling; Wang, Yun-Cui; Ai, Ya-Ting; Wang, Ling; Gu, Si-Meng; Wang, Ping; Long, Qing-Hua; Hu, Hui (Frontiers in Pharmacology, 2021)
Qiangji Decoction (QJD), a classic formula, has been widely used to treat brain aging-related neurodegenerative diseases. However, the mechanisms underlying QJD’s improvement in cognitive impairment of neurodegenerative diseases remains unclear. In this study, we employed D-galactose to establish the mode of brain aging by long-term D-galactose subcutaneous injection. Next, we investigated QJD’s effect on cognitive function of the mode of brain aging and the mechanisms that QJD suppressing neuroinflammation as well as improving neurodegenerative changes and hippocampal neuron apoptosis. The mice of brain aging were treated with three different dosages of QJD (12.48, 24.96, and 49.92 g/kg/d, respectively) for four weeks. Morris water maze was used to determine the learning and memory ability of the mice. HE staining and FJB staining were used to detect the neurodegenerative changes. Nissl staining and Tunel staining were employed to detect the hippocampal neuron apoptosis. The contents of TNF-α, IL-1β and IL-6 in the hippocampus were detected by using ELISA. Meanwhile, we employed immunofluorescence staining to examine the levers of GFAP and IBA1 in hippocampus. Besides, the protein expression levels of Bcl-2, Bax, Caspase-3, Cleaved Caspase-3, AMPKα, p-AMPKα-Thr172, SIRT1, IκBα, NF-κB p65, p-IκBα-Ser32 and p-NF-κB p65-Ser536 in the hippocampus of different groups were detected by Western blot (WB). Our findings showed that the QJD-treated groups, especially the M-QJD group mitigated learning and memory impairments of the model of brain aging as well as improvement of neurodegenerative changes and hippocampal neuron apoptosis. Moreover, the M-QJD markedly attenuated the neuroinflammation by regulating AMPK/SIRT1/NF-κB signaling pathway. Taken together, QJD alleviated neurodegenerative changes and hippocampal neuron apoptosis in the mode of brain aging via regulating AMPK/SIRT1/NF-κB signaling pathway.